2010
DOI: 10.1111/j.1399-3062.2010.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis in the early post-transplant period after kidney transplantation: clinical features and therapeutic management

Abstract: Visceral leishmaniasis (VL) is a rare complication of kidney transplantation, with <100 cases reported in the literature. It is a life-threatening condition and usually occurs as a late complication after transplantation, with a median delay of 18 months between transplantation and onset of disease. We report the clinical features and management of 5 kidney transplant recipients who presented with VL in the early post-transplant period. All patients were successfully treated with liposomal amphotericin B (L-AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 13 publications
0
41
0
1
Order By: Relevance
“…Overall,~20% of VL cases (n = 6) were diagnosed within the first 3 months after transplantation, and two cases were diagnosed within the first 30 days. A recent report suggested that during early disease onset, transmission is related to the reactivation of a dormant infection, when immunosuppression is at its highest level [18]. Despite this risk, VL screening is not routinely performed because the value of serologic and molecular screening of asymptomatic donors and recipients remains unclear [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Overall,~20% of VL cases (n = 6) were diagnosed within the first 3 months after transplantation, and two cases were diagnosed within the first 30 days. A recent report suggested that during early disease onset, transmission is related to the reactivation of a dormant infection, when immunosuppression is at its highest level [18]. Despite this risk, VL screening is not routinely performed because the value of serologic and molecular screening of asymptomatic donors and recipients remains unclear [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Transplantlı hastalarda viseral leyiş-manyoz primer enfeksiyon şeklinde olabileceği gibi immün süpresif tedaviyle sessiz enfeksiyonun reaktivasyonu sonucunda da gelişebilir 12 . Viseral leyişmanyoz, solid organ transplantasyonlu hastaların %22-37.5'inde tedavinin ilk yılında sıklıkla tekrarlamaktadır 13 . Çalışmamızda böbrek nakli uygulanmış bir olgumuzda dört kez viseral leyişman-yoz reaktivasyonu görülmüş ve olgu son atağında nozokomiyal enfeksiyon nedeniyle kaybedilmiştir.…”
Section: Discussionunclassified
“…The excretion of amphotericin B, pentamidine isethionate and miltefosine in breast milk is [93][94][95][96][97][98]103,[107][108][109][110][111][112][113][114] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…An 83-year-old patient with myelodysplastic syndrome was treated successfully with liposomal amphotericin for CL caused by Leishmania major without adverse effects 112 . Renal transplantation patients presenting with VL also had a good response to liposomal amphotericin 110,113 . However, toxicity occurred in patients with LV after heart transplantation, and treatment needed to be interrupted 114 .…”
Section: Human Immunodefi Ciency Virus/acquired Immunodefi Ciencymentioning
confidence: 99%